A bibliometric analysis of undergraduate theses submitted to the Far Eastern University - Dr. Nicanor Reyes Medical Foundation from A.Y. 2009-2009 to 2014-2015 - Gonzales, Leanna Marie D.G (2016)
The medical education and training today have increased in complexity, requiring more information than ever before. Therefore, libraries must frequently develop and evaluate their collection to continue to provide the users with the best services and most updated and reliable information that they need.